The last letter - Yarros, Rebecca (Amara, an imprint of Entangled Publishing, LLC, 2019)
When Ryan dies in Afghanistan, he leaves a letter asking that his friend Beckett watch over his sister, Ella. Beckett has already been corresponding with her under his nickname, Chaos, and after leaving the service he goes to visit Ella, who is the mother of twins. One of the twins has been diagnosed with leukemia, and Ella is dealing with the illness while running a business-- singlehandedly. When Beckett becomes part of Ella's life, will his promise to watch over her bloom into something more? --